Health and illness in the experience of Church of Scotland ministers, 1930-1969 - Eadie, Hugh Angus (The University of Edinburgh, 1971)
The following dissertation reports the findings of a three-year research project concerning "health and illness in the experience- of Church of Scotland ministers,- 1930-1969". It was conducted against a "background of growing concern that the health of this clergy group may have deteriorated significantly in a number of respects in recent years. There was, however, little evidence, "beyond personal impressions and limited statistical data, and no previous research to justify this concern or to substantiate the 'popular' assumptions, which this concern implied. This programme was then instigated with a view to conducting a multilateral investigation into various dimensions of the health experience of this group of clergymen and with the object of providing a spring-board from which more detailed, microscopic studies in this field could subsequently be initiated. Part I is devoted to an extensive discussion of the frame of reference within which this investigation was conducted. Consideration is given to the background for this inquiry in terms of the importance of health in the minister's life and work and in terms of previous research conducted elsewhere. The basic principles and assumptions involved in the concept of Total Health, which is intrinsic to the conceptual orientation of this inquiry, and the evaluative criteria which arise out of this concept are established. The case is argued for the adoption of an holistic and multidimensional conceptualization of health, which pays due regard to the multidimensional unity and ambiguity of life in the experience of the whole person within a particular 'world'. Following from this conceptual foundation, the case is argued for the application of a multilateral, eclectic methodology, broadly based on the principles of Existential Analysis and designed to investigate health from different perspectives. The following segments of the dissertation, Parts II, III, and IV present the findings of the three-phase research programme carried out between October 1967 and August 19&9* Part II attempts a description and analysis of the salient structures and characteristics of the Church of Scotland minister's 'world' and 'life-style', especially as these conditions could bear on the individual's health. This initial phase of th^ programme provides no. information about ministers' health per se, but does serve to distinguish these particular clergymen as an occupational and denominational group and also establishes the context within which all their experiences of health and illness need, to be considered. Part III reports the. findings of a detailed statistical study of mortality and morbidity in the experience of Church of Scotland ministers. This segment of the dissertation is concerned with the effects and end-results of being a Church of Scotland minister as these are manifested in death and disablement. Statistical data of' this kind provides a foundation of empirical evidence from which to make an evaluation of the health of this clergy group and includes valuable comparative data. Attention is then directed, in Part V, to an examination of the personal health experience of Church of Scotland parish ministers. This examination is conducted on the basis of a survey of a representative sample of parish ministers, with the object of investigating the physical, intrapersonal, interpersonal, and vocational dimensions of the individual minister's health experiences. The principal conclusions which may be drawn from the evidence elicited by this three-phase research programme are then surveyed in Part V. There is good reason to conclude, in the first-instance, that Church of Scotland ministers generally enjoy an unusually favourable standard of health by comparison with members of other professions (teachers excepted) and with the Scottish male population. This applies particularly to the physical dimension of their health; but it is also true that no conclusive evidence has come forward to suggest that these ministers are unusually vulnerabl'e to mental, psychoneurotic, or personality disorders and difficulties. In general, the. reputation of Church of Scotland ministers for sound health is fully justified by the available evidence: as a group, they e$joy notable longevity, a low rate of death (especially up to the age of 45 years), low rates of death from most major causes of-death (especially from diseases of the respiratory system) in the general population, and few deaths or incapacitating disabilities from diseases and disorders directly attributable to neglect, detrimental personal habits, unsatisfactory standards of hygiene, or unfavourable working and living conditions. It seems reasonable to conclude that their faith-commitment, strong sense of personal responsibility and stewardship, observance of positive personal habits, and the external conditions of their life and work have an integrative effect and contribute to the positive health record of these.ministers. The only respect, and it is quite outstanding, in which the health experience of these ministers is significantly unfavourable is the excessive incidence of coronary heart disease as the major cause of mortality and morbidity among them. There is no immediate explanation for this phenomenon. Against this favourable background, there is some evidence to suggest, secondly,'that there has been a decline in the health of Church of Scotland ministers: a decline which can be traced back to the' mid-1950s, but which has become more prominent since 1960. This deterioration has been most apparent in'the 55-64 age group, with an increasing rate of death, proportionately more deaths and cases of disablement from coronary heart disease, a higher proportion of disablement in younger age groups from psychiatric disorders, and a lower average age of death overall. However, it is emphasized that the magnitude and significance of these developments should not be over-stated. The .decline has not been dramatic or on a large-scale and it remains true, in comparative terms, that Church of Scotland ministers constitute a relatively healthy group. Then, thirdly, it is concluded that the main sources of disruption and disintegration in the experience of Church of Scotland ministers are associated with intrapersonal, interpersonal, and vocational factors. and processes, and are closely associated with the emotional stresses, and intrapersonal conflicts to which they are frequently subject. The cumulative effect of these stresses and conflicts becomes manifest in the psychoneurotic, personality, and psychosomatic symptoms and disorders experienced by these ministers. Particular attention is given to the disintegrative effects of conflicts which these men commonly experience in relation to the relative demands of ultimate commitment and proximate responsibilities ("existential-ontological tension") and in relation to their oscillations between the polarities of freedom and responsibility, holiness and humanity, and isolation and intimacy. Consideration is also given to the theoretical possibility that the integrative ana disintegrative experiences of Church of Scotland ministers may be closely related to a common "guilt-neurosis syndrome", in which personality factors and intrapersonal processes are predominant but which also involves interpersonal, social, occupational, and vocational factors.in a dynamic and intricate process of interaction. Then, finally, the dissertation concludes with a speculative theological postscript, setting the health of Church of Scotland ministers within a much wider existential-ontological perspective and tentatively exploring the theme of a basic conflict between processes of self-destruction and self-acceptance.
A study of health and illness in the experience of Church of Scotland ministers, 1930-1969